2022
DOI: 10.3390/su14084654
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Financial Feasibility of an OTEC Ecopark: A Case Study at Cozumel Island

Abstract: The aim of this article is to show how an OTEC Ecopark could provide comprehensive, sustainable, and quality products that satisfy the diverse needs of coastal communities in Mexico. An offshore 60 MW hybrid Ocean Thermal Energy Conversion (OTEC) plant is proposed, which will provide products that will not only fulfill the water, energy, and food needs of the coastal communities, but also energize the local blue economy. An assessment of the financial feasibility of the plant as well as a comparative analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
(106 reference statements)
0
7
0
Order By: Relevance
“…The combination of DOW and surface ocean water is done because of the temperature-sensitive nature of sea grapes. Following the development, an eco-park will be built in Mexico, to meet the growing food demand around Cozumel Island, Mexico (Tobal-Cupul et al, 2022). This will be done by developing OTEC-Offshore Seaweed Aquaculture through the cultivation of Ulva spp.…”
Section: Otec Environmental Impactmentioning
confidence: 99%
“…The combination of DOW and surface ocean water is done because of the temperature-sensitive nature of sea grapes. Following the development, an eco-park will be built in Mexico, to meet the growing food demand around Cozumel Island, Mexico (Tobal-Cupul et al, 2022). This will be done by developing OTEC-Offshore Seaweed Aquaculture through the cultivation of Ulva spp.…”
Section: Otec Environmental Impactmentioning
confidence: 99%
“…However, distributed generation (on-site generation) has been gaining importance as renewable energies are developed (Gorr-Pozzi et al, 2021). Off-grid systems and mini-grids or microgrids can generate electricity efficiently Gorr-Pozzi et al, 2021;Olmedo-González et al, 2021;Tobal-Cupul et al, 2022). Note: The power units are "normalized" because the graph only represents the power variation considering a minimum power generation of 0.5 units.…”
Section: Off-grid Hybrid Systems For Marine Renewable Energy Harvestingmentioning
confidence: 99%
“…Capacity Factor (%) (Garduño-Ruiz et al, 2021;Gorr-Pozzi et al, 2021;IEA-OES, 2022;Tobal-Cupul et al, 2022) Off grid system viability (Power rating) (Sheng et al, 2017;IRENA, 2019IRENA, , 2020Gorr-Pozzi et al, 2021) Efficiency (W/m 2 ) (Alcérreca-Huerta et al, 2019;Hernández-Fontes et al, 2019) Environmental Climate change potential (gCO2 equiv/kWh) (Rau and Baird, 2018;Paredes et al, 2019;Ma et al, 2022;Smoot, 2022;Tobal-Cupul et al, 2022) Affection to threatened ecosystem (% of affection) Exclusion zone (m 2 ) (Kim et al, 2012;Gourvenec et al, 2022;Hernández Galvez et al, 2022) Frontiers in Energy Research frontiersin.org contributed to manuscript revision, read, and approved the submitted version.…”
Section: Author Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that OTEC systems are economically viable in regions where the surface seawater temperature is greater than 25 • C. On the other hand, Ref. [31] presents the design of an OTEC Ecopark consisting of a 60 MW OTEC system coupled to a marine aquaculture farm located near the Island of Cozumel. The proposed system meets part of the needs of coastal communities for energy production, desalinated water and food production.…”
Section: Introductionmentioning
confidence: 99%